Daniel Lind-Ramos: Standing (De Pie) in Loíza - Fiet, Lowell (2015)
The accomplished african-puerto rican artist Daniel Lind-Ramos paints on canvas with oil, brushes, and spatulas, meticulously blending colors, layering textures, and shaping images. He also works with common cardboard, wire screen, discarded appliances, car parts, the refuse of coconut palm trees, broken musical instruments and used articles of everyday domestic and agricultural labor. Local artisans in his hometown of Loíza, the seat of Puerto Rico’s African cultural heritage, use these materials as well to create the dynamic masks of the characters for the annual Fiestas of Santiago Apóstol.